The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.26603/001c.21311
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Common Methodologies for the Determination of Knee Flexor Muscle Strength

Abstract: Background Knee flexion strength may hold important clinical implications for the determination of injury risk and readiness to return to sport following injury and orthopedic surgery. A wide array of testing methodologies and positioning options are available that require validation prior to clinical integration. The purpose of this study was to 1) investigate the validity and test-retest reliability of isometric knee flexion strength measured by a fixed handheld dynamometer (HHD) apparatus compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…There is also concern of inaccuracy when testing large muscle groups such as the knee extensors using HHD 1 88. This finding is consistent with systematic reviews on healthy and injured individuals13 and applies also for knee flexor strength tests 95…”
Section: Discussionsupporting
confidence: 73%
“…There is also concern of inaccuracy when testing large muscle groups such as the knee extensors using HHD 1 88. This finding is consistent with systematic reviews on healthy and injured individuals13 and applies also for knee flexor strength tests 95…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have reported that isometric and concentric knee flexion torque was significantly greater with the ankle dorsiflexed position than the plantarflexed position (Ogborn et al, 2021;Marchetti et al, 2019;Miller et al, 1996;Croce et al, 2000). Since the gastrocnemius is a biarticular muscle, it is thought that ankle dorsiflexion stretches the gastrocnemius and brings it closer to its optimal length, which contributes to knee flexion strength and knee joint stability, thereby enabling greater muscle force (Miller et al, 1996;Croce et al, 2000) In NHE strength testing, it was thought that the ankle dorsiflexed position was suitable for exerting greater peak eccentric force than the plantarflexed position; but, our results differed from the hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…Hamstring strength may be affected by ankle position, as a previous study reported that isometric knee flexion torque was 14-22% greater with the ankle dorsiflexed position than the plantarflexed position (Ogborn et al, 2021;Marchetti et al, 2019). Similarly, concentric knee flexion torque (angular velocity of 60°/s) was 7-13% greater with the ankle dorsiflexed position than the plantarflexed position (Miller et al, 1996;Croce and Miller, 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Maximal voluntary isometric contraction (MVIC) of the knee extensors and knee flexors was measured pre, immediately post intervention and at 3 months follow-up, with the unaffected contralateral limb tested prior to the KOA limb at each assessment. The participants were seated with their knees flexed at 60 degrees (−30 degrees from full knee extension) and the hip joint at 85 degrees on an isokinetic dynamometer (Biodex System 4 Pro, Biodex Medical Systems, Shirley, NY, USA), which has an intraclass correlation coefficient (ICC) of 0.93 for knee extension and an ICC of 0.89 for knee flexion [ 27 ]. Knee flexion of 60 degrees was selected to ensure consistency between testing sessions and participants; 60 degrees of knee flexion results in the greatest force output following and bypassing any potential restriction in movement due to KOA.…”
Section: Methodsmentioning
confidence: 99%